May Day in the Dome - Souvenir Programme, 2000 (2000)
2000 1960-2000 "May Day in the Dome - Souvenir Programme, 2000" [T0547.jpg], 2000, Trades Union Congress On the May Day Bank Holiday, the TUC negotiated a half price entrance ticket to the Millennium Dome in South East London and organised a series of special events and activities. 32,500 people came the second highest attendance figure for the Dome throughout the year.